STRATEGI MANAJEMEN BIMBINGAN DAN KONSELING DI MADRASAH ALIYAH NEGERI 2 HULU SUNGAI UTARA - Ahriadi Ahriadi; Abdul Wahab Syakhrani (CV. ADIBA ASIHA AMIRA, 2025)
This study is based on the background that the implementation of management strategies is needed by BK teachers in determining guidance and counseling service strategies, so that it is easier for BK teachers to help students. This study aims to determine the guidance and counseling management strategy at State Islamic Senior High School 2 Hulu Sungai Utara in overcoming problems faced by students. This type of research is qualitative research. The subjects of this study were 2 BK teachers, the object of this study was the guidance and counseling management strategy at State Islamic Senior High School 2 Hulu Sungai Utara. Data collection techniques used observation, interviews, and documentaries. Data were processed using editing, classification, and interpretation techniques. Data were analyzed using a qualitative approach and inductive conclusions were drawn. The results of the study showed that the guidance and counseling management strategy in overcoming problems faced by students at State Islamic Senior High School 2 Hulu Sungai Utara can be seen from the process carried out by BK teachers, namely the process of formulation, implementation, and evaluation of strategies. The results of the guidance and counseling management strategy at State Islamic Senior High School 2 Hulu Sungai Utara in overcoming problems faced by students are first, the strategies applied in overcoming student problems, namely information services, individual counseling, and group counseling. Second, its usefulness is to help BK teachers take a systematic and professional approach in solving student problems, and to help ensure that the services provided are structured, eflective, and can meet student needs. The third supporting factor is the availability of facilities for BK, supported by the principal, deputy head of student aflairs, homeroom teachers, other teachers, OSIM supervisors, and PIK-R MAN 2 HSU. Fourth, the inhibiting factor is that there is no special schedule for the implementation of guidance and counseling in classes, so it requires free hours and time outside of class hours.